2018
DOI: 10.1177/0300060518765846
|View full text |Cite
|
Sign up to set email alerts
|

Wolff-Parkinson-White syndrome and noncompaction in Leber’s hereditary optic neuropathy due to the variant m.3460G>A

Abstract: This report describes a 66-year-old Caucasian male who acutely developed severe, bilateral impairment of visual acuity at 24 years of age. Leber’s hereditary optic neuropathy (LHON) was suspected but the diagnosis was not genetically confirmed until the age of 49 years when the primary LHON mutation m.3460G>A was detected. Since onset, visual acuity had slightly improved. The family history was positive for LHON (brother, two sisters of mother, female cousin) and genetically confirmed in his brother and one au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Other mitochondrial disorders that frequently combine cardiac disease and movement disorders, such as ataxia, dystonia, tremor, or spastic paraparesis include Leigh syndrome, Leber hereditary optic neuropathy, neuropathy, ataxia, and retinitis pigmentosa (NARP) syndrome as well as certain oxidative phosphorylation and respiratory chain disorders, such as coenzyme Q10 deficiency. These are frequently overlapping syndromes caused by alterations in both nuclear and mitochondrial genes involved in energy metabolism, frequently presenting hypertrophic or dilated cardiomyopathy, arrhythmias, and cardiac conduction defects 2,139–143 . Detailed cardiac manifestations of these disorders can be found in Tables 1 and 2 and Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other mitochondrial disorders that frequently combine cardiac disease and movement disorders, such as ataxia, dystonia, tremor, or spastic paraparesis include Leigh syndrome, Leber hereditary optic neuropathy, neuropathy, ataxia, and retinitis pigmentosa (NARP) syndrome as well as certain oxidative phosphorylation and respiratory chain disorders, such as coenzyme Q10 deficiency. These are frequently overlapping syndromes caused by alterations in both nuclear and mitochondrial genes involved in energy metabolism, frequently presenting hypertrophic or dilated cardiomyopathy, arrhythmias, and cardiac conduction defects 2,139–143 . Detailed cardiac manifestations of these disorders can be found in Tables 1 and 2 and Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…These are frequently overlapping syndromes caused by alterations in both nuclear and mitochondrial genes involved in energy metabolism, frequently presenting hypertrophic or dilated cardiomyopathy, arrhythmias, and cardiac conduction defects. 2,[139][140][141][142][143] Detailed cardiac manifestations of these disorders can be found in Tables 1 and 2 and Table S1.…”
Section: Mitochondrial Disordersmentioning
confidence: 99%
“…Current treatment options for the management of supraventricular tachyarrhythmias can be used in patients with mtDNA-D. In case of symptomatic ventricular preexcitation with recurrent episodes of AVNRT, accessory pathway ablation has been successfully performed in patients with mtDNA-D. 40,41,90,91 In asymptomatic patients with intermittent ventricular preexcitation, the role of electrophysiological study (EPS) and catheter accessory pathway ablation is more controversial. Although data are lacking, there is general consensus that catheter ablation of accessory pathway should be performed in asymptomatic patients in whom invasive EPS risk stratification identifies high-risk properties, according to current guidelines.…”
Section: Supraventricular Tachyarrhythmiasmentioning
confidence: 99%
“…Case reports have found left ventricular hypertrabeculation in patients with LHON [176,177]. Another study showed a statistically significant longer QTc in LHON subjects from one American family when compared to controls [178,179]. Other cardiac associations reported include WPW (~9% of LHON subjects) and myocardial thickening (Table 1) [177,179,180,181].…”
Section: Primary Mitochondrial Disordersmentioning
confidence: 99%